Influence of indigenous galactogogue on performance of sows and piglets and related economics - S, Ganesh Kumar; Singh, Mukesh; Dutt, Triveni; Patel, M; Mandal, A B; Kumar, Sanjay; Mondal, S K (The Indian Journal of Animal Sciences, 2012)
The study was carried out to study the effect of indigenous galactogogue on the body weight gains of sow’s body weight and piglets during lactation and to work out on relative economics. Landrace × Desi sows (8) along with their piglets were randomly divided into 2 groups i.e. T1 and T2 (control and treated with galactogogue). Each sow of T1 and T2 had 14.3 and 13.8 piglets at birth, respectively. Body weight of sows was nonsignificantly influenced by treatment, however, total body weight losses during lactation differed significantly. Feed intake of sows up to weaning was not influenced by the treatment. Wean-to-heat interval was not significantly influenced by the treatment. Effect of galactogogue treatment on litter size and litter weight at birth, at weaning was nonsignificant. However, total litter weight at weaning was lower in T1 than T2. Mean weaning weight of each piglet in T2 was significantly higher than T1. The treatment influenced feed intake of piglets significantly, while pre-weaning mortality of piglets was not significantly influenced. No significant difference in serum glucose and protein was found between the treatments. Net benefit / sow was ` 115.22 and ` 587.82 in T1 and T2, respectively. It can be concluded that indigenous galactogogue treatment significantly improved weaning weight of piglets and reduced lactational weight loss in sows as well as it was found to be economically advantageous over control group.